Can trust be restored to high-street banking: A 20-year challenge? - Peter McCormack; Jonathan Deacon (Cogent Business & Management, 2017)
This article is based on a dissertation submitted for an MSc in Marketing submitted by the first author and supervised by the second author. It is a viewpoint article that highlights the complexity of the challenge of restoring trust to high-street/retail banking, and explores some of the related issues of conduct risk, ethics and culture. It includes a brief historical analysis reflecting structural change in the mid-1980s up to today with a link to some current thoughts and research, and concludes that the banking sector's current ambitions to restore trust are likely to be flawed and unlikely to deliver in the timelines that the banks and regulators expect. The article concludes with a number of related issues/subjects that are worthy of further research and flags some particular questions in the conclusion.
Keywords: 650